COMPUTATION HERITAGE APPLICATIONS HUSBAND OR WIFE ACCORDING TO ISLAMIC LAW USING VISUAL BASIC 6.0 PROGRAMMING LANGUAGE - Halimah Halimah; Irfan, Skom, MMSI Irfan, Skom, MMSI (Jurnal Sistem Informasi, 2002)
Calculation of Inheritance in Islam in the control of Al-Quran and Al-Hadith in detailand clear and the rules are created directly by God Almighty that the truth is not indoubt, do not like the law that created by humans which so many flaws andweaknesses. Which raised the feeling of dissatisfaction that ultimately arise theproblems that are not in want. Calculation of the legacy by using the computer will beeasier and the results will be quicker.